2016
DOI: 10.4067/s0718-221x2016005000054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weathering on physical and mechanical properties of hybrid nanocomposite based on polyethylene, woodflour and nanoclay

Abstract: Wood plastic composites have received increasing attention during the last decades, because of many advantages related to their use. However the durability of Wood plastic composites after ultraviolet exposure has become a concern. In this research, hybrid nanocomposites of polyethylene and woodflour with different concentrations of nanoclay were fabricated using melt compounding followed by injection molding. Specimens were exposed for 2000 h to ultraviolet radiation and moisture cycling in a laboratory weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The composite modulus is often a property of particular interest (Punyamurthy et al 2014, AlMaadeed et al 2014b. The improvement in composite modulus is an expected outcome because the reinforcement effect caused by the wood flour addition (Eshraghi et al 2016). It is clearly seen that the composite modulus increased with the wood flour loading.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite modulus is often a property of particular interest (Punyamurthy et al 2014, AlMaadeed et al 2014b. The improvement in composite modulus is an expected outcome because the reinforcement effect caused by the wood flour addition (Eshraghi et al 2016). It is clearly seen that the composite modulus increased with the wood flour loading.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In addition, they have been widely used as automotive parts, building applications and consumer products (Hong et al 2014, Eshraghi et al 2016, Tufan et al 2016, Teuber et al 2016. However, most thermoplastics are hydrophobic while wood flour is hydrophilic.…”
Section: Introductionmentioning
confidence: 99%
“…The water content M(t) absorbed by each specimen was then calculated as the mass gain percent relative to its initial weight ( w 0 ) as follows: M(),t=(),wtw0w0×100 where w t is the sample weight after time t. Specimens were immersed up to 120 days in water.…”
Section: Experimental Workmentioning
confidence: 99%
“…Also, results showed that weathering decreased modulus of elasticity values; however, good dispersion of nanoclay layers resulted in slight drop of modulus of elasticity values. Likewise, Chang studied the effects of nano‐silica addition on water uptake of glass fiber/epoxy composites . Nano‐silica addition was found to reduce the sample water uptake when compared with that of unfilled glass fiber/epoxy composite specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the flexural modulus reduced by about 10 % with respect to the initial values after one year of weathering. Eshraghi et al (2016) also observed about 10 % decline in flexural modulus of HDPE-wood composites after 2000 h of artificial weathering. It was observed that the loss in flexural modulus in the composites containing smaller wood particle size (Mesh size -100) was relatively lesser as compared to other two wood particle sizes.…”
Section: Effect Of Natural Weathering On Mechanical Properties Of Wpcsmentioning
confidence: 71%